EVALUASI PENGELOLAAN OBAT PROGRAM HIV DI UPTD INSTALASI FARMASI DINAS KESEHATAN KOTA PEMATANGSIANTAR TAHUN 2024 - Lili Aprila; Ismi Noer Farida, Isma Oktadiana (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Drug management includes planning, storage and distribution is one of the important tasks of the UPTD Pharmacy Installation of the Pematangsiantar City Health Office. Drug management includes planning, storage and distribution is one of the important tasks of the UPTD Pharmacy Installation of the Pematangsiantar City Health Office. Poor drug management will have a negative impact on service quality. The purpose of this study was to evaluate the management of program drugs for Human Immunodefeciency Virus (HIV) in 2023 at the UPTD Pharmacy Installation of the Pematangsiantar City Health Office. The research was conducted in July - August 2024. This research is descriptive with data obtained retrospectively and concurrently. The data obtained were analyzed using indicators and compared with the results of the study. The results showed that the planning, storage and distribution of HIV program drugs at the UPTD Pharmacy Installation of the Pematangsiantar City Health Office had not fully met the standard indicators. This is indicated by 3 indicators that have not met the standards, namely the level of drug availability; percentage of expired drugs; average drug vacancy time and 1 indicator has met the standards, namely the drug storage system. The conclusion of this study is that drug planning at the UPTD Pharmaceutical Installation of the Pematangsiantar City Health Office is planned based on the average use of drugs for 3 months. Drug storage uses the First In First Out (FIFO) / First Expired First Out (FEFO) system. The distribution of drugs at the UPTD Pharmaceutical Installation of the Pematangsiantar City Health Office is based on requests made by the person in charge of drugs at Puskesmas, Clinics and Hospitals through the SIHA 2.1 application. The destruction of drugs at the UPTD Pharmacy Installation of the Pematangsiantar City Health Service will be carried out in 2021 and at this time there are no known plans for the further destruction of drugs.